Bacteriocinogenic lactic acid bacteria from Thai fermented foods: Potential food applications. (April 2023) - Woraprayote, Weerapong; Janyaphisan, Thitiphorn; Adunphatcharaphon, Saowalak; Sonhom, Nipon; Showpanish, Kittiya; Rumjuankiat, Kittaporn; Visessanguan, Wonnop; Elliott, Christopher T.; Petchkongkaew, Awanwee
Abstract: Fermentation is an ancient preservation process which has been widely used in many countries across the world, especially in Southeast Asia. Many types of traditional fermented food products that contain lactic acid bacteria (LAB) appear to contain an abundance of bacteriocin producers. Until now, thirteen types of traditional Thai fermented food are recognized as isolation sources of bacteriocinogenic LAB. Furthermore, twenty-four bacteriocins from Thai fermented food isolates have been identified and fully charactized. Additionally, six bacteriocinogenic LAB strains have been applied to food products, as starter cultures or bacteriocin preparations, in order to increase product quality and safety. However, research into this form of application of bacteriocins produced by Thai fermented food isolates in food products remains very limited. Hence, the aim of this article is to provide a comprehensive review on bacteriocin from Thai fermented food isolates (i.e., definition, types diversity, and various isolation sources of bacteriocinogenic LAB). Additionally, the potential application of bacteriocins as either starter cultures or preservatives has also been summarized. Highlights: Many traditional fermented foods contain lactic acid bacteria (LAB) which are also bacteriocin producers. Twenty-four bacteriocins from Thai fermented food isolates have been fully characterized. Utilization of bacteriocinogenic and/or bacteriocin preparations in food products could enhance food safety and reduce food waste.